A Study of Clinical and Etiological Profile of Anaemia in Geriatric Patients in a Tertiary Care Hospital (Academia Journal of Medicine, 2019)
Background: Geriatric anemia is a global health problem because of its high prevalence and associated significant morbidity and mortality. Aim: The objectives of this study were to estimate the pattern of anemia in the elderly patients and the underlying etiology of anemia. Subjects  and Methods: This was a hospital-based prospective observational study, conducted in patients aged 60 years and above at SSIMS, T. Begur.  Anemia is defined as hemoglobin level less than 13 g/dl in men and 12 g/dl in women. Results: Among the 100 older patients with anemia, the  mean value of hemoglobin was 8.9 ± 2.3 g/dl. The etiological distribution of anemia was iron deficiency in 25 patients (25%), chronic disease  in 22 patients (22%), hematological disorders in 20 (20%), chronic kidney disease in 12 (12%), multifactorial in 8 (8%), vitamin B12  deficiency in 3 (3%), folate deficiency in 1 (1%), and hypothyroidism in 1 patient (1%). No etiology could be found in 8 patients (8%). 57.6%  of the iron-deficient patients had upper gastrointestinal lesions and 30.7% had a nutritional cause. Common chronic diseases causing anemia  were malignancy (36.6%) and liver disease (29.1%). The myelodysplastic syndrome was the commonest hematological disorder. 53.35% of the  patients had normocytic anemia, 40% had microcytic anemia, and 6.6% had macrocytic anemia. Conclusion: In most of the cases, anemia in  the elderly had a treatable cause. Thus, a thorough investigation including gastrointestinal endoscopy is warranted. Unexplained progressive or  unresponsive anemia requires bone marrow examination.
Keywords: Anemia; elderly; geriatrics